Cardiovascular disease risk exacerbates brain aging among Hispanic/Latino adults in the SOL-INCA-MRI Study - Stickel, Ariana M.; Tarraf, Wassim; Gonzalez, Kevin A.; Paredes, Alejandra Morlett; Zeng, Donglin; Cai, Jianwen; Isasi, Carmen R.; Kaplan, Robert; Lipton, Richard B.; Daviglus, Martha L.; Testai, Fernando D.; Lamar, Melissa; et al. (Frontiers in Aging Neuroscience, 2024)
Background: Cardiovascular disease (CVD) risk factors are highly prevalent among Hispanic/Latino adults while reports on the prevalence of MRI infarcts are not well documented. We, therefore, sought to examine the relationships between CVD risk factors and infarcts with brain structure among Hispanic/Latino individuals. Methods: Participants included 1,886 Hispanic/Latino adults (50-85 years) who underwent magnetic resonance imaging (MRI) as part of the Study of Latinos - Investigation of Neurocognitive Aging-MRI (SOL-INCA-MRI) study. CVD risk was measured approximately 10.5 years prior to MRI using the Framingham Cardiovascular Risk Score, a measure of 10-year CVD risk (Low (<10%), Medium (10-<20%) and High (≥20%)). MR infarcts were determined as present or absent. Outcomes included total brain, cerebral and lobar cortical gray matter, hippocampal, lateral ventricle, and total white matter hyperintensity (WMH) volumes. Linear regression models tested associations between CVD risk and infarct with MRI outcomes and for modifications by age and sex. Results: Sixty percent of participants were at medium or high CVD risk. Medium and high CVD risk were associated with lower total brain and frontal gray matter and higher WMH volumes compared to those with low CVD risk. High CVD risk was additionally associated with lower total cortical gray matter and parietal volumes and larger lateral ventricle volumes. Men tended to have greater CVDRF-related differences in total brain volumes than women. The association of CVD risk factors on total brain volumes increased with age equal to an approximate 7-year increase in total brain aging among the high CVD risk group compared to the low risk group. The presence of infarct(s) was associated with lower total brain volumes which was equal to an approximate 5-year increase in brain aging compared to individuals without infarcts. Infarcts were also associated with smaller total cortical gray matter, frontal, and parietal volumes and larger lateral ventricle and WMH volumes. Conclusions: The high prevalence of CVD risk among Hispanic/Latino adults may be associated with accelerated brain aging.